Comparison of the Wound‐Healing Effects of Ginsenosides, their Metabolites, and Aglycones. (17th December 2015) - Park, Jun Yeon; You, Hwan; Lee, Dahae; Huh, Wonsang; Hwang, Gwi Seo; No, Kyoung Tai; Kim, Ki Hyun; Ham, Jungyeob; Yamabe, Noriko; Kim, Younghoon; Kang, Ki Sung
Abstract : Abstract : The effect of ginsenosides, their metabolites, and aglycones on tube formation in human umbilical vein vascular endothelial cells (HUVEC) was investigated to identify ways to potentially enhance wound healing. Of the tested compounds, sapogenins, aglycones of ginsenosides, promoted tube formation, whereas ginsenosides and their metabolites had no effect or inhibitory effects on tube formation. Treatment of HUVEC at concentrations of 6.25 and 12.5 μM 20( S )‐protopanaxadiol (PPD) significantly increased tube formation by 34 and 35%, respectively. PPD also had a pronounced effect on the speed of wound closure in mouse dermal wounds.